Application of amino acid type ionic liquid and lubricating liquid composition

By using amino acid-type ionic liquids, especially glutamate-phytic ionic liquids, the problem of difficult ultralubrication in high load and high humidity environments is solved, and significant friction reduction and energy saving effects are achieved.

CN119463939APending Publication Date: 2025-02-18JIANGSU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411422396.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve superlubrication under high load and high humidity environments, resulting in increased friction and energy loss.

Method used

The use of amino acid-type ionic liquids as lubricants, especially glutamic acid-phytic ionic liquids, achieves superlubrication under high load and high humidity conditions through its unique hydrogen bond network structure.

Benefits of technology

Under high load and high humidity environments, superlubrication can be achieved after a brief run-in, significantly reducing the coefficient of friction, improving equipment efficiency and reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463939A_ABST
    Figure CN119463939A_ABST
Patent Text Reader

Abstract

The invention discloses an application of amino acid type ionic liquid as a lubricant. Amino acid in the amino acid type ionic liquid is used as a hydrogen bond acceptor. The invention also provides a lubricating liquid composition which comprises the following components in percentage by mass: 90-98% of amino acid type ionic liquid and the balance of water. The invention further provides a method for achieving super lubrication, and the method comprises the steps that the surface of the friction pair is coated with the lubricant, and super lubrication is achieved after running-in; the friction conditions are as follows: the load is 1-5N, the temperature is 20-25 DEG C, the linear speed is 0.026-0.105 m / s, and the friction time is greater than or equal to 10s; the friction pair is silicon nitride / silicon dioxide; the molar ratio of the glutamic acid to the phytic acid ionic liquid is 1: 2; the lubricant comprises the following components in percentage by mass: 98-100% of glutamic acid-phytic acid ionic liquid and the balance of water. According to the invention, the amino acid type ionic liquid is used as the lubricant, so that the obvious antifriction and antiwear effects can be achieved, and particularly, the glutamic acid-phytic acid ionic liquid can realize super lubrication under the conditions of high load and high humidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating materials, and in particular relates to the application of amino acid type ionic liquids and lubricating liquid compositions. Background Art

[0002] Friction is undoubtedly one of the most common, yet most interesting, physical phenomena we encounter in our daily lives. However, approximately one fifth of the energy consumed on Earth each year is used to overcome friction in systems and processes ranging from automobiles to manufacturing. Therefore, mitigating and controlling friction is of great importance in saving useful energy, increasing the service life of mechanical equipment, and reducing the impact on the environment.

[0003] Superlubrication is a lubrication state in which the friction force is almost zero or even completely disappears. In fact, due to the interference of the external environment and the limitations of detection technology, the lubrication state when the friction coefficient is less than 0.01 can be considered as superlubrication. Superlubrication technology provides a feasible solution for saving energy and reducing economic losses. The low surface energy and specific micro-nano structure of the superlubrication surface make it have extremely low surface adhesion and friction coefficient. This characteristic makes superlubrication technology have important applications in lubricants, aircraft surfaces, medical equipment, food processing equipment and other fields, and can be used to reduce energy loss and improve equipment efficiency. At present, patents have disclosed the application of ionic liquids as superlubricants. For example, the composition based on choline-type ionic liquids disclosed in the invention patent with application number 202210456231.8 can achieve superlubrication under a load of 1-3N, but it cannot achieve superlubrication under a larger load and high humidity environment. This is because the high humidity environment will cause the water content in the lubricant to increase and the viscosity of the lubricant to decrease; under high load conditions, the carrying capacity of the lubricant is reduced, and the contact surface cannot be effectively separated, resulting in increased friction.

[0004] In addition, compared with the lubricant prepared by adding natural organic acid to synthetic lubricating oil disclosed in the invention patent with application number 202111457707.1, the lubricating liquid of the present invention can achieve super lubrication under higher loads and further shorten the running-in period. In addition, the lubricating liquid also exhibits excellent tribological properties under high humidity, so it has a wider application value.

[0005] Therefore, providing a lubricating fluid that can achieve super lubrication under high load and high humidity conditions will help expand the application of lubricating fluids in more scenarios, which is of great significance. Summary of the invention

[0006] Based on the above technical problems, the present invention provides the use of amino acid-type ionic liquids as lubricants and lubricating fluid compositions based on amino acid-type ionic liquids, which can achieve superlubrication after a short period of running under high load and high humidity conditions.

[0007] The specific scheme of the present invention is as follows:

[0008] One of the purposes of the present invention is to provide an application of an amino acid type ionic liquid as a lubricant, wherein the amino acid in the amino acid type ionic liquid serves as a hydrogen bond acceptor.

[0009] Preferably, the amino acid type ionic liquid is selected from a combination of one or more of amino acid-organic acid ionic liquids, amino acid-choline salt ionic liquids, amino acid-alcohol ionic liquids, and amino acid-sugar ionic liquids. More preferably, the amino acid type ionic liquid is an amino acid-organic acid ionic liquid.

[0010] Preferably, in the amino acid type ionic liquid, the hydrogen bond acceptor is glutamic acid or glycine, and the hydrogen bond donor is phytic acid; the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:1 to 1:4.

[0011] Preferably, the amino acid type ionic liquid is a glutamic acid-phytic acid ionic liquid, wherein the molar ratio of glutamic acid to phytic acid is 1:2.

[0012] Preferably, amino acid-type ionic liquid is used as a lubricant for silicon nitride / silicon dioxide friction pairs, and super lubrication can be achieved when used in an environment with a load of 1-5N and a humidity of 20-70%.

[0013] The second object of the present invention is to provide a lubricating fluid composition, which comprises, by mass percentage, 90-98% of an amino acid type ionic liquid and the remainder of water.

[0014] Preferably, the composition comprises, by mass percentage, 95-98% of amino acid type ionic liquid and the remainder of water.

[0015] Preferably, the amino acid type ionic liquid is selected from one or more combinations of amino acid-organic acid ionic liquids, amino acid-choline salt ionic liquids, amino acid-alcohol ionic liquids, and amino acid-sugar ionic liquids.

[0016] Preferably, the amino acid type ionic liquid is a glutamic acid-phytic acid ionic liquid, wherein the molar ratio of glutamic acid to phytic acid is 1:2.

[0017] The third object of the present invention is to provide a method for achieving superlubrication, comprising: applying a lubricant to the surface of a friction pair, and achieving superlubrication after running-in; the friction conditions include: a load of 1-5N, a temperature of 20-25°C, a linear speed of 0.026-0.105m / s, and a friction time of ≥10s; the friction pair is silicon nitride / silicon dioxide; the molar ratio of the glutamic acid-phytic acid ionic liquid is 1:2; the lubricant includes, by mass percentage: 98-100% of the glutamic acid-phytic acid ionic liquid and the remainder is water.

[0018] The beneficial effects of the present invention are:

[0019] The present invention proposes the use of amino acid type ionic liquid as a lubricant. The amino acid type ionic liquid as a lubricant can achieve significant friction reduction and anti-wear effects. The amino acid type ionic liquid, especially the lubricating liquid composition containing glutamic acid-phytic acid ionic liquid, can achieve super lubricity after a short run-in under high load and high humidity conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a curve showing the change of the friction coefficient of the lubricant described in Example 1 over time;

[0021] Figure 2 is the superlubricity duration of the lubricant described in Example 1;

[0022] Figure 3 is the average friction coefficient of the lubricant described in Example 1 under different loads;

[0023] Figure 4 is the average friction coefficient of the lubricant described in Example 1 at different linear speeds;

[0024] Figure 5 The curve of the friction coefficient of the lubricant described in Example 1 under high humidity (60%-70%) over time;

[0025] Figure 6 is a curve showing the change of the friction coefficient of the lubricant described in Example 2 over time;

[0026] Figure 7 is a curve showing the change of the friction coefficient of the lubricant described in Example 3 over time;

[0027] Figure 8 is a curve showing the change of the friction coefficient of the lubricating fluid composition described in Example 4 over time;

[0028] Fig. 9 is a curve showing the change of the friction coefficient of the lubricating fluid composition described in Example 5 over time;

[0029] Fig.10 is a curve showing the change of the friction coefficient of the lubricating fluid composition described in Example 6 over time;

[0030] Fig.11 is a curve showing the change of the friction coefficient of the lubricant described in Example 7 over time;

[0031] Fig.12 is a curve showing the change of the friction coefficient of the lubricant described in Example 8 over time;

[0032] Fig.13is a curve showing the change of the friction coefficient of the lubricant described in Example 9 over time;

[0033] Fig.14 is a curve showing the change of the friction coefficient of the lubricant described in Example 10 over time;

[0034] Fig.15 is a curve showing the change of the friction coefficient of the lubricant described in Example 11 over time;

[0035] Fig.16 is a curve showing the change of the friction coefficient of the lubricant described in Comparative Example 1 over time;

[0036] Fig.17 The curve of the friction coefficient of the lubricant in Comparative Example 2 under high humidity (60%-70%) over time;

[0037] Fig.18 It is the average friction coefficient of the lubricant composition of Comparative Example 3 under different loads. DETAILED DESCRIPTION

[0038] The ionic liquid described in the present invention refers to a low-melting mixture formed by two or more compounds, which is accompanied by electrically neutral ligands during its synthesis. The neutral ligands and ions are complexed to form a hydrogen bond network and can exist stably in liquid form within a wide temperature range.

[0039] There is no specific limitation on the preparation method of the ionic liquid. For example, a conventional one-step synthesis method is used to simply mix and heat the component raw materials to form a uniform and stable liquid. For example, the glutamic acid-phytic acid ionic liquid involved in the following examples is obtained by mixing glutamic acid and phytic acid in a certain proportion, heating to 60° C., and stirring for 1 hour.

[0040] The friction performance test method of the lubricating fluid in the following examples and comparative examples is as follows: a high temperature friction and wear tester (MPX-3G) is used, the upper friction pair is a silicon nitride ball with a diameter of 5 mm, and the lower friction pair is silicon dioxide. Before each experiment, 50 μL of lubricating fluid is dripped on the silicon dioxide with disposable plastic. If there is no special explanation, the experimental conditions are: load of 5N, temperature of 25°C, linear speed of 0.078m / s, humidity of 30-40%, and friction radius of 5mm.

[0041] Hereinafter, the technical solution of the present invention will be described in detail through specific embodiments, but it should be clearly stated that these embodiments are for illustration and are not to be construed as limiting the scope of the present invention.

[0042] Example 1

[0043] Application of glutamic acid-phytic acid ionic liquid as lubricant, wherein the molar ratio of glutamic acid to phytic acid in the glutamic acid-phytic acid ionic liquid is 1:2.

[0044] The friction performance of the glutamic acid-phytic acid ionic liquid as a lubricant in this embodiment was tested by the above method. The change curve of the friction coefficient over time is shown in FIG. Figure 1 shown.

[0045] It can be seen that super lubrication is achieved after a short run. Figure 1 The curve of the friction coefficient changing with time within 60 minutes is only shown. In fact, the experimental results show that the friction coefficient of the ionic liquid described in this embodiment as a lubricant can be stabilized below 0.01 within 150 minutes. The super-lubricity duration of the lubricant described in this embodiment is as follows: Figure 2 shown.

[0046] The average friction coefficient of the lubricant under different loads (linear speed 0.078 m / s) is as follows: Figure 3 As shown. It can be seen that within the load range of 2-5N, this lubricant has good super lubricity.

[0047] The average friction coefficient of the lubricant at different linear speeds (load 5N) is as follows: Figure 4 It can be seen that within the speed range of 0.052-0.105 m / s, the friction coefficient of this lubricant reaches the lowest, and super lubrication can be achieved when the line speed is about 0.078 m / s.

[0048] The friction coefficient of the lubricant described in this embodiment at a higher humidity (60%-70%) is as follows: Figure 5 As shown. It can be seen that in a high humidity environment, this lubricant still has good super lubricity.

[0049] Example 2

[0050] Application of glutamic acid-phytic acid ionic liquid as lubricant, wherein the molar ratio of glutamic acid to phytic acid in the glutamic acid-phytic acid ionic liquid is 1:1.

[0051] The friction performance of the glutamic acid-phytic acid ionic liquid as a lubricant in this embodiment was tested by the above method. The change curve of the friction coefficient over time is shown in FIG. Figure 6 shown.

[0052] It can be seen that when the glutamic acid-phytic acid ionic liquid described in this embodiment is used as a lubricant, the friction coefficient is low, but super lubrication cannot be achieved.

[0053] Example 3

[0054] Application of glutamic acid-phytic acid ionic liquid as lubricant, wherein the molar ratio of glutamic acid to phytic acid in the glutamic acid-phytic acid ionic liquid is 1:4.

[0055] The friction performance of the glutamic acid-phytic acid ionic liquid as a lubricant in this embodiment was tested by the above method. The change curve of the friction coefficient over time is shown in FIG. Figure 7 shown.

[0056] It can be seen that when the glutamic acid-phytic acid ionic liquid described in this embodiment is used as a lubricant, superlubrication can be achieved after a short period of running, but the superlubrication state is relatively short in stability.

[0057] Example 4

[0058] A lubricating liquid composition comprises, by mass percentage, 98% of glutamic acid-phytic acid ionic liquid and the remainder of water; wherein in the glutamic acid-phytic acid ionic liquid, the molar ratio of glutamic acid to phytic acid is 1:2.

[0059] The friction performance of the lubricating fluid composition described in this embodiment was tested by the above method. The curve of the change of friction coefficient over time is as follows: Figure 8 shown.

[0060] Example 5

[0061] A lubricating liquid composition comprises, by mass percentage, 95% of glutamic acid-phytic acid ionic liquid and the remainder of water; wherein in the glutamic acid-phytic acid ionic liquid, the molar ratio of glutamic acid to phytic acid is 1:2.

[0062] The friction performance of the lubricating fluid composition described in this embodiment was tested by the above method. The curve of the change of friction coefficient over time is as follows: Fig. 9 shown.

[0063] Example 6

[0064] A lubricating liquid composition comprises, by mass percentage, 90% of glutamic acid-phytic acid ionic liquid and the remainder of water; wherein in the glutamic acid-phytic acid ionic liquid, the molar ratio of glutamic acid to phytic acid is 1:2.

[0065] The friction performance of the lubricating fluid composition described in this embodiment was tested by the above method. The curve of the change of friction coefficient over time is as follows: Fig.10 shown.

[0066] Depend on Figure 8-10It can be seen that the lubricating liquid composition obtained by adding 2% water to the glutamic acid-phytic acid ionic liquid can achieve superlubricity after a short period of running, but the stability and average friction coefficient are not as good as the pure ionic liquid lubricant without water; on this basis, the water content is further increased to 10%. Although the friction coefficient is lower, superlubricity cannot be achieved.

[0067] Embodiment 7-9

[0068] Application of glutamic acid-alcohol ionic liquid as lubricant, wherein the molar ratio of glutamic acid to alcohol is 1:2; in Example 7, the alcohol is ethylene glycol; in Example 8, the alcohol is polyethylene glycol; in Example 9, the alcohol is propylene glycol.

[0069] The friction performance of the glutamic acid-alcohol ionic liquid as a lubricant described in Examples 7-9 was tested using the above method. The experimental conditions were adjusted to: load 3N, temperature 25°C, and linear speed 0.078m / s. The curve of the change of friction coefficient over time is shown in Figure 11-13 As shown, they correspond to Examples 7-9 respectively.

[0070] It can be seen that although the friction coefficient of glutamic acid-alcohol ionic liquids as lubricants is low, they cannot achieve superlubrication after a short running-in.

[0071] Example 10

[0072] Application of glutamic acid-choline ionic liquid as lubricant, wherein choline is choline chloride, and the molar ratio of glutamic acid to choline chloride is 1:2. The curve of the change of friction coefficient over time is as follows Fig.14 shown.

[0073] It can be seen that although the friction coefficient of glutamic acid-choline chloride ionic liquid as a lubricant is low, it cannot achieve super lubrication. And the friction coefficient gradually increases over time.

[0074] Embodiment 11

[0075] This example discusses the friction performance of the ionic liquid described in Example 1 under different friction pairs. Specifically, the friction pair is replaced by steel / steel from silicon nitride / silicon dioxide in Example 1. The other friction performance test methods are the same as those in Example 1. The obtained curve of the change of friction coefficient over time is as shown in FIG. Fig.15 shown.

[0076] It can be seen that when the ionic liquid described in Example 1 is used for the silicon nitride / silicon dioxide friction pair, superlubrication is achieved after a short running-in period, but when the friction pair is replaced with steel / steel, although the friction coefficient is lower, superlubrication cannot be achieved.

[0077] Comparative Example 1

[0078] Example 2 of the invention patent with application number 202111457707.1 discloses a lubricant composition, which is used as comparative example 1. The lubricant composition includes 0.5g of phytic acid and 10g of polyalkylene glycol aqueous solution (polyalkylene glycol content is 35wt%) by mass.

[0079] The curve of the friction coefficient of the lubricant described in this comparative example under a load of 3N (other test conditions remain unchanged) over time is as follows: Fig.16 shown.

[0080] The lubricant described in this comparative example can achieve superlubricity under 3N conditions, but cannot achieve superlubricity under high load conditions.

[0081] Comparative Example 2

[0082] Application of choline chloride-1-5-pentanediol ionic liquid as a lubricant, wherein the molar ratio of 1-5-pentanediol to choline chloride is 3:1.

[0083] The curve of the friction coefficient of the lubricant described in this comparative example under high humidity (60%-70%) conditions (other test conditions remain unchanged) over time is as follows: Fig.17 shown.

[0084] It can be seen that under high humidity conditions, the lubricant described in this comparative example cannot achieve super lubricity.

[0085] Comparative Example 3

[0086] Example 1 in the invention patent with application number 202210456231.8 discloses a lubricant composition, which is used as comparative example 3 of the present application. The lubricant composition comprises, by mass percentage: 98% of choline chloride-magnesium chloride hexahydrate ionic liquid and 2% of deionized water.

[0087] Fig.18 The average friction coefficient of the lubricant composition of this comparative example under different loads (linear speed 100 mm / s). As can be seen from the figure, within the load range of 1N-3N, the lubricant composition of comparative example 3 has good super lubricity; however, under a load of 4N-5N, super lubricity cannot be achieved.

[0088] In summary, the lubricant of the present invention can achieve super lubrication under conditions of greater humidity and higher load, and the materials used are low-cost and easy to prepare.

[0089] Table 1 shows the lubricants, friction pairs and friction coefficients used in each embodiment.

[0090]

[0091]

[0092] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Application of amino acid type ionic liquid as lubricant, characterized in that: The amino acids in the amino acid-type ionic liquid serve as hydrogen bond acceptors.

2. The use according to claim 1, characterized in that: The amino acid type ionic liquid is selected from a combination of one or more of amino acid-organic acid ionic liquids, amino acid-choline salt ionic liquids, amino acid-alcohol ionic liquids, and amino acid-sugar ionic liquids; preferably, the amino acid type ionic liquid is an amino acid-organic acid ionic liquid.

3. The use according to claim 1 or 2, characterized in that: In the amino acid type ionic liquid, the hydrogen bond acceptor is glutamic acid or glycine, and the hydrogen bond donor is phytic acid; the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:1 to 1:

4.

4. The use according to any one of claims 1 to 3, characterized in that: The amino acid type ionic liquid is a glutamic acid-phytic acid ionic liquid, wherein the molar ratio of glutamic acid to phytic acid is 1:

2.

5. The use according to any one of claims 1 to 4, characterized in that: Amino acid-type ionic liquid is used as a lubricant for silicon nitride / silicon dioxide friction pairs, and super lubrication can be achieved when used in an environment with a load of 1-5N and a humidity of 20-70%.

6. A lubricating fluid composition, characterized in that: According to the mass percentage, it comprises: 90-98% of amino acid type ionic liquid and the balance of water.

7. The lubricating fluid composition according to claim 6, characterized in that: According to the mass percentage, it comprises: 95-98% of amino acid type ionic liquid and the balance of water.

8. The lubricating fluid composition according to claim 6 or 7, characterized in that: The amino acid type ionic liquid is selected from one or more combinations of amino acid-organic acid ionic liquids, amino acid-choline salt ionic liquids, amino acid-alcohol ionic liquids, and amino acid-sugar ionic liquids.

9. The lubricating fluid composition according to any one of claims 6 to 8, characterized in that: The amino acid type ionic liquid is a glutamic acid-phytic acid ionic liquid, wherein the molar ratio of glutamic acid to phytic acid is 1:

2.

10. A method for achieving superlubrication, characterized in that: include: The lubricant is coated on the surface of the friction pair, and super lubrication is achieved after running-in; the friction conditions include: load 1-5N, temperature 20-25°C, linear speed 0.026-0.105m / s, friction time ≥10s; the friction pair is silicon nitride / silicon dioxide; the molar ratio of the glutamic acid-phytic acid ionic liquid is 1:2; the lubricant includes, by mass percentage: glutamic acid-phytic acid ionic liquid 98-100%, and the balance is water.

Citation Information

Patent Citations

  • A liquid lubricant, its preparation method and application, and a method for rapidly achieving superlubricity.

    CN114085699B

  • Applications of choline-type ionic liquids as lubricants and lubricant compositions

    CN114806673B